Chest X-ray findings of COVID-19 pneumonia in children: Experiences in a multicenter study in Thailand. - Aunya Kulbun; Prakarn Tovichien; Chanapai Chaiyakulsil; Araya Satdhabudha; Harutai Kamalaporn; Kanokkarn Sunkonkit; Rattapon Uppala; Watit Niyomkarn; Vasinee Norasettekul; Kanokpan Ruangnapa; Chutima Smathakanee; Bararee Choursamran; et al. (PLoS ONE, 2024)
Introduction Although chest X-ray is commonly used to diagnose COVID-19 pneumonia, few studies have explored findings in pediatric patients. This study aimed to reveal chest X-ray characteristics in children with COVID-19 pneumonia and compare between non-severe and severe cases. Methods This multicenter, nationwide retrospective study included all children aged 0 to 15 years who were admitted to 13 medical facilities throughout Thailand with COVID-19 pneumonia between January 2020 and October 2021. We analyzed the demographics, clinical features, and chest X-ray results of these children, and compared differences between the non-severe and severe groups. Results During the study period, 1018 children (52% male, median age 5 years) were admitted with COVID-19 pneumonia. Most chest radiographic findings showed bilateral (51%) patchy/ground glass opacities (61%) in the central area (64%). Only 12% of the children exhibited typical classification for COVID-19 pneumonia, whereas 74% of chest radiographs were categorized as indeterminate. Comorbidities including chronic lung diseases [adjusted OR (95%CI): 14.56 (3.80-55.75), P-value <0.001], cardiovascular diseases [adjusted OR (95%CI): 7.54 (1.44-39.48), P-value 0.017], genetic diseases [adjusted OR (95%CI): 28.39 (4.55-177.23), P-value <0.001], clinical dyspnea [adjusted OR (95%CI): 12.13 (5.94-24.77), P-value <0.001], tachypnea [adjusted OR (95%CI): 3.92 (1.79-8.55), P-value 0.001], and bilateral chest X-ray infiltrations [adjusted OR (95%CI): 1.99 (1.05-3.78), P-value 0.036] were factors associated with severe COVID-19 pneumonia. Conclusion Most children with COVID-19 pneumonia had indeterminate chest X-rays according to the previous classification. We suggest using chest X-rays in conjunction with clinical presentation to screen high-risk patients for early detection of COVID-19 pneumonia.